The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s40621-020-00281-y
|View full text |Cite
|
Sign up to set email alerts
|

The changing epidemiology of dog bite injuries in the United States, 2005–2018

Abstract: Background In 2018, the most recent year for which data are available, dog bites ranked as the 13th leading cause of nonfatal emergency department visits in the United States. As dog ownership spirals upwards in the United States, it is important to continue to monitor the epidemiology of dog bite injuries. This study provides contemporary data on the incidence of dog bites injuries in the United States and in New York and profiles individuals who have been treated for dog bites in emergency departments. The s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 7 publications
5
17
0
Order By: Relevance
“…Lower-income patients may seek care in ED more frequently for minor injuries relative to those with higher incomes, for reasons related to medical literacy, access to care, and insurance coverage (Kutner et al 2003 ); as such, this group may present with a higher proportion of lower-acuity injuries overall relative to the middle two quartiles. Nonetheless our findings compare with data suggesting that dog bite injuries (regardless of severity) are associated with lower socioeconomic status (Loder 2019 ; Rhea et al 2014 ; Tuckel and Milczarski 2020 ). Income may serve as a proxy for factors which correlate with dog bite injury.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Lower-income patients may seek care in ED more frequently for minor injuries relative to those with higher incomes, for reasons related to medical literacy, access to care, and insurance coverage (Kutner et al 2003 ); as such, this group may present with a higher proportion of lower-acuity injuries overall relative to the middle two quartiles. Nonetheless our findings compare with data suggesting that dog bite injuries (regardless of severity) are associated with lower socioeconomic status (Loder 2019 ; Rhea et al 2014 ; Tuckel and Milczarski 2020 ). Income may serve as a proxy for factors which correlate with dog bite injury.…”
Section: Discussionsupporting
confidence: 73%
“…Income may serve as a proxy for factors which correlate with dog bite injury. For example, income correlates with rurality and may also serve as a proxy for pet ownership or family size (where a larger family may prevent closer supervision of individual children) (Loder 2019 ; Tuckel and Milczarski 2020 ). Additionally, dog breed factors may play a role in explaining our findings in relation to income and insurance status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study developed in Italy reported mongrel dogs as the most frequently breed involved in accidents with children ( 12 ), which agrees with our study. Among the reported breeds, Pit Bull was the most prevalent, which agrees with most of the literature ( 7 , 14 , 17 , 22 25 , 27 , 28 , 30 , 32 , 33 , 35 ). Curiously, Poodle dogs were the third breed most cited, despite being a breed considered suitable for families with children and not highly reported in the literature about dog bites.…”
Section: Discussionsupporting
confidence: 89%
“…Our study showed that boys are more likely to be bitten by dogs, this fact had been previously reported ( 3 , 5 , 7 , 12 15 , 17 , 18 , 24 , 25 , 27 30 ). To the best of our knowledge, only one large study developed in the United States of America reported a higher number of girls involved in accidents with dogs ( 6 ).…”
Section: Discussionsupporting
confidence: 88%